Impact of Vaccination on Cost and Course of Hospitalization Associated with COVID-19 Infection. Issue 1 (25th January 2023) - Somani, Selina T.; Firestone, Rachelle L.; Donnelley, Monica A.; Sanchez, Luciano; Hatfield, Chad; Fine, Jeffrey; Wilson, Machelle D.; Duby, Jeremiah J.
Abstract: Objective: Examine the impact of vaccination status on hospital cost and course for patients admitted with COVID-19 infection. Design: Retrospective cohort study characterizing vaccinated and unvaccinated individuals hospitalized for COVID-19 between April 2021 to January 2022. Setting: Large academic medical center. Methods: Patients were included if they were greater than 18 years old, fully vaccinated or unvaccinated against COVID-19, and admitted for COVID-19 infection. Patients: 437 consecutively admitted patients for COVID-19 infection met inclusion criteria. Of these, 79 were excluded for unknown or partial vaccination status, transfer from an outside hospital, or multiple COVID-19 related admissions. Results: Overall, 279 (77.9%) unvaccinated patients compared to 79 (22.1%) vaccinated patients were hospitalized with a diagnosis of COVID-19. Average length of stay was significantly lower in the vaccinated group (6.47 days versus 8.92 days, P = 0.03). Vaccinated patients experienced a 70.6% lower risk of ICU admission (OR = 0.29, 95% CI 0.12–0.71, P = 0.006). The unadjusted cost of hospitalization was not found to be statistically significant ($119, 630 versus $191, 146, P = 0.06). After adjusting for age and comorbidities, vaccinated patients experienced a 26% lower cost of hospitalization compared to unvaccinated patients ( P = 0.004). Unvaccinated patients incurred a significantly higher cost of hospitalization per day ($29, 425 vs $13, 845 P < 0.0001). Unvaccinated patients (n = 118, 42.9%) were more likely than vaccinated patients (n = 16, 20.3%) to require high-flow oxygen or mechanical ventilation (OR = 2.95, 95% CI 1.62–5.38, P = 0.0004). Conclusion: Vaccinated patients experienced a lower cost of hospitalization after adjusting for age and comorbidities and shorter length of stay compared to unvaccinated patients admitted for COVID-19.